Constructing a population-based research database from routine maternal screening records: a resource for studying alloimmunization in pregnant women. - Brian K Lee (Public Library of Science (PLoS), 2011)
Background Although screening for maternal red blood cell antibodies during pregnancy is a standard procedure, the prevalence and clinical consequences of non-anti-D immunization are poorly understood. The objective was to create a national database of maternal antibody screening results that can be linked with population health registers to create a research resource for investigating these issues. Study design and methods Each birth in the Swedish Medical Birth Register was uniquely identified and linked to the text stored in routine maternal antibody screening records in the time window from 9 months prior to 2 weeks after the delivery date. These text records were subjected to a computerized search for specific antibodies using regular expressions. To illustrate the research potential of the resulting database, selected antibody prevalence rates are presented as tables and figures, and the complete data (from more than 60 specific antibodies) presented as online moving graphical displays. Results More than one million (1,191,761) births with valid screening information from 1982-2002 constitute the study population. Computerized coverage of screening increased steadily over time and varied by region as electronic records were adopted. To ensure data quality, we restricted analysis to birth records in areas and years with a sustained coverage of at least 80%, representing 920,903 births from 572,626 mothers in 17 of the 24 counties in Sweden. During the study period, non-anti-D and anti-D antibodies occurred in 76.8/10,000 and 14.1/10,000 pregnancies respectively, with marked differences between specific antibodies over time. Conclusion This work demonstrates the feasibility of creating a nationally representative research database from the routine maternal antibody screening records from an extended calendar period. By linkage with population registers of maternal and child health, such data are a valuable resource for addressing important clinical questions, such as the etiological significance of non-anti-D antibodies.